New Exact Solutions for High Dispersive Cubic-Quintic Nonlinear Schrödinger Equation - Yongan Xie; Shengqiang Tang (Journal of Applied Mathematics)
We study a class of high dispersive cubic-quintic nonlinear Schrödinger equations, which describes the propagation of femtosecond light pulses in a medium that exhibits a parabolic nonlinearity law. Applying bifurcation theory of dynamical systems and the Fan sub-equations method, more types of exact solutions, particularly solitary wave solutions, are obtained for the first time.